Kepastian dan Perlindungan Hukum terhadap Data Pribadi Pengguna Fintech Peer To Peer Lending - Hendri Hendri; Suriyanto Suriyanto; Resi Pranacitra (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The Information Technology-Based Mutual Funding Service Industry (LPBBTI) or known as Fintech P2P Lending is in great demand by the unbanked, this has attracted many illegal P2P lending platforms to also enliven this industry. One of the legal problems that arose later was the misuse of personal data of loan users carried out by the illegal online loan providers. This research was conducted using the normative legal method (library study). The results of this study are a form of legal protection for personal data of fintech peer to peer lending users in terms of the applicable laws and regulations in Indonesia, including preventive legal protection. In Preventive legal protection on online lending and borrowing services based on financial technology, the government issued several regulations related to fintech peer to peer lending, namely POJK LPBBTI and SEOJK LPMUBTI Governance. In addition, there is also repressive protection which has a function to resolve disputes in the future through the Court within the scope of General Courts or through Government Agencies which are administrative appeal institutions by providing administrative sanctions for perpetrators of violations. Efforts that can be taken by fintech peer to peer lending users if they find that there has been a leak of user personal data on the platform of the fintech peer to peer lending provider, that is, they can take non-judicial or non-litigation (out of court) legal remedies or judicial or litigation (judicial) legal remedies.